EKSPLORASI KERAGAMAN DAN KAJIAN TAKSONOMI PTERIDOPHYTA SEBAGAI POTENSI EKOWISATA DI KAWASAN PUNCAK DULAMAYO KABUPATEN GORONTALO - Febriyanti Febriyanti (Biology Department, Mathematics and natural science, Tadulako University, 2022)
English translation. This study aims to find out the diversity of pteridophyta species and their taxonomic studies based on morphological character and analysis of Pteridophyta phenetic relationships in the peak area of Dulamayo Gorontalo Regency through exploration and interview methods. Exploration was conducted to obtain species diversity data and taxonomic data of pteridophyta by identifying and recording all morphological characteristics of pteridophyta (Rhizome, Ptiolus and Lamina) found at the research site. Further identification of the micromorphological character of pteridophyta (Scales and Trioma) was carried out at the Laboratory of Botany Of Biology Faculty of MIPA Gorontalo State University. Determination of pteridophyta diversity index using Sahon Wiener formula while phenetic relationship data is analyzed using gower General Similarity Coefficient formula on MVSP softwere. Based on the results of the study obtained 13 species of nail plants that have morphological character variations with a diversity index of H'= 1,087 which fall into the moderate category, namely species Asplenium trichomane, Phymatosorus scolopendria, Christella parasitica and Nephrolepis cordifolia found in kawsan waterfall UPSA, species Sphaerostephanos unitus, Dicksonia circutaria, Balantium antarcticum, Polybotrya alfredii, Pneumatopteris costata, Dryopteris filix-mas, Cyathea arborea, Nephrolepis biserrate and Sellaginella willdenowii are found in the Arboretum. The genetic distance obtained from the analysis of kinship relationships with the phenotic method is at a coefficient of 66% (0.69) which divides into two main clusters based on morphological character similarities.